Negative ion antibacterial polyester fiber fabric and preparation method thereof
By optimizing the formulation of composite negative ion powder, antibacterial agent and dispersant, and adjusting the preparation process of polyester fiber, the negative ion release, antibacterial properties and mechanical properties of polyester fiber fabrics are improved, and the problems of low mechanical strength and poor long-lasting antibacterial properties of the fabric are solved.
Patent Information
- Application Number
- CN202411789496.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
During use, polyester fiber fabrics have problems such as low mechanical strength and poor long-lasting antibacterial properties, which affects their application in life.
By controlling the component ratio and particle size of the composite negative ion powder, optimizing the parameter conditions of the composite antibacterial agent, preparing a mixture of improved dispersant and coupling agent, adjusting the temperature and time of the esterification polycondensation reaction, and controlling the parameter conditions during the textile process to improve the negative ion release, antibacterial ability, overburn strength, wear resistance and elongation of break of the fabric.
The fabric's negative ions are continuously released, the antibacterial effect is improved, the mechanical properties are enhanced, the wear resistance and the elongation of break are improved, and the problems of low mechanical strength and poor long-lasting antibacterial properties of polyester fiber fabrics are solved.
Smart Images

Figure CN119593093A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber fabrics, in particular to a negative ion antibacterial polyester fiber fabric and a preparation method thereof. Background Art
[0002] Polyester fiber is a synthetic fiber obtained by spinning polyester formed by the polycondensation of organic dibasic acid and diol, and is a high molecular compound. Polyester fiber has many advantages, including high breaking strength, moderate resilience, good heat resistance and light resistance. Polyester fiber can maintain a stable shape under various conditions of use, making the fabric washable and wear-resistant, making polyester fiber widely used in home textiles and other fields. However, polyester fiber has poor moisture absorption performance and is prone to bacteria, which limits the development of polyester fiber in many occasions.
[0003] Introducing negative ion additives into polyester fibers is a common technology to improve antibacterial ability. When negative ion polyester fiber fabrics rub against human skin, they will continuously produce negative air ions, which can eliminate odors, purify the air, and have antibacterial and antifungal effects. However, there is still a problem of particle agglomeration during the synthesis process, resulting in unclear modification effects.
[0004] Patent CN112442745B discloses a method for preparing a polyester having a temperature-responsive negative ion release and antibacterial function and its fiber. The invention adopts a new negative ion release / antibacterial mechanism to prepare a new negative ion release / antibacterial fiber, the fiber diameter can be ultrafine, the fiber can be made white / light-colored, and has a permanent negative ion release / antibacterial function. However, the negative ion release / antibacterial fiber of the invention is prone to agglomeration when used in the preparation of polyester fiber, thereby affecting the duration of negative ion release and the antibacterial effect, resulting in poor long-term antibacterial performance of the polyester fiber.
[0005] Patent CN107217325A discloses a negative ion, antibacterial and anti-mite composite polyester functional fiber and its manufacturing method. The composite polyester functional fiber is light and comfortable, has health functions such as negative ion and antibacterial and anti-mite, and has broad application prospects; the preparation method of the polyester fiber is simple, low cost, low equipment requirements, and suitable for large-scale production. However, the polyester fiber prepared by this method has low mechanical strength and poor washing resistance, and is difficult to use for a long time.
[0006] In summary, after introducing negative ion additives into polyester fibers and weaving them into fabrics, there will be disadvantages such as difficulty in continuous release of negative ions, unstable bactericidal effect and easy wear, which makes the polyester fiber fabric have low mechanical strength and poor long-lasting antibacterial properties, seriously affecting its application in life.
[0007] Therefore, a negative ion antibacterial polyester fiber fabric and a preparation method thereof are proposed. Summary of the invention
[0008] The purpose of the present invention is to design a negative ion antibacterial polyester fiber fabric and a preparation method thereof. The present invention overcomes the problems of low mechanical strength and poor lasting antibacterial performance of polyester fiber fabrics; the synthetic raw materials of the negative ion antibacterial polyester fiber include composite negative ion powder, composite antibacterial agent, improved dispersant, coupling agent mixture, terephthalic acid, ethylene glycol and catalyst auxiliary agent. The present invention enables the negative ions of the fabric to be continuously released by controlling the proportion of components and particle size in the composite negative ion powder; improves the continuous antibacterial ability of the fabric by changing the amount of the composite negative ion powder and the parameter conditions for synthesizing the composite antibacterial agent; improves the bursting strength of the fabric by preparing an improved dispersant, changing the amount of the coupling agent mixture and the proportion of the components in the coupling agent mixture; improves the wear resistance of the fabric by controlling the amount of ethylene glycol and the catalyst auxiliary agent and the temperature and time of the esterification polycondensation reaction; and improves the elongation at break of the fabric by controlling the parameter conditions in the textile process.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] In one aspect, the present invention provides a negative ion antibacterial polyester fiber fabric, wherein the negative ion antibacterial polyester fiber fabric comprises the following raw materials in parts by weight:
[0011] Composite negative ion powder: 4-8 parts;
[0012] Composite antibacterial agent: 1.1-1.5 parts;
[0013] Improved dispersant: 0.7-1.5 parts;
[0014] Coupling agent mixture: 1-5 parts;
[0015] Terephthalic acid: 40 parts;
[0016] Ethylene glycol: 14-22 parts;
[0017] Catalyst aid: 0.08-0.12 parts.
[0018] Preferably, the composite negative ion powder is a mixture of tourmaline powder, quartz powder and carbon fiber; the weight ratio of the tourmaline powder, the quartz powder and the carbon fiber is 3-9:2:1; and the particle size of the composite negative ion powder is 450nm-650nm.
[0019] Preferably, the coupling agent mixture is a mixture of γ-aminopropyltriethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl)aluminate; the weight ratio of the γ-aminopropyltriethoxysilane, the tetrabutyl titanate and the tri(2-vinylphenyl)aluminate is 5-7:3:7-5.
[0020] Preferably, the catalyst promoter is one of antimony trioxide, titanium tetrachloride and zinc chloride.
[0021] Another aspect of the present invention provides a method for preparing a negative ion antibacterial polyester fiber fabric, the method for preparing a negative ion antibacterial polyester fiber fabric comprising the following steps:
[0022] S1: 40 parts of terephthalic acid, 14-22 parts of ethylene glycol and 0.08-0.12 parts of a catalyst promoter are placed in a beaker and stirred for 1 hour to obtain a mixture A; the mixture A is transferred to an esterification polycondensation reactor and heated at a temperature of TE 1 The reaction was continued for 1.5 h to obtain ethylene terephthalate;
[0023] S2: adding 4-8 parts of composite anion powder, 1.1-1.5 parts of composite antibacterial agent, 0.7-1.5 parts of improved dispersant and 1-5 parts of coupling agent mixture to the ethylene terephthalate, stirring until uniformly mixed to obtain mixture B; transferring the mixture B to an esterification polycondensation reactor, reacting at 260° C. for 50 min, then adjusting the esterification polycondensation reactor to vacuum, and heating to temperature TE 2 Polycondensation 1 time, and then the polyester chips are obtained by cooling and pelletizing;
[0024] S3: drying the polyester chips and transferring them to a vacuum drum, slowly heating them to a temperature TE 3 Pre-crystallization was carried out for 100 min, and then the temperature was raised to TE 4 Keep TI 2 time, and then put it into the spinning machine at a temperature of TE 5 The spinning process is carried out at a spinning speed of 3100 m / min to obtain negative ion antibacterial polyester fibers; the negative ion antibacterial polyester fibers are woven to obtain the negative ion antibacterial polyester fiber fabrics.
[0025] Preferably, the temperature TE in S1 is 1 It is 220℃-232℃.
[0026] Preferably, the preparation method of the composite antibacterial agent in S2 is: 6-10 parts of nano-titanium dioxide, 1-5 parts of silver ions and 2-6 parts of copper nitrate are placed in 15 parts of deionized water and stirred for 1 hour, then transferred to a reactor and reacted at 175°C-190°C for 10 hours, cooled to room temperature and centrifuged to obtain the composite antibacterial agent.
[0027] Preferably, the preparation method of the improved dispersant described in S2 is: put 1-9 parts of polyvinyl alcohol fatty acid ester and 5 parts of polyvinyl alcohol into 10 parts of deionized water, stir evenly to obtain a dispersant mixture; add 0.6-1 part of glutaraldehyde to the dispersant mixture, stir evenly to obtain a precursor; put the precursor into a reactor for cross-linking reaction at a temperature of 125°C-140°C for 150 minutes, cool to room temperature and centrifuge to obtain the improved dispersant.
[0028] Preferably, the vacuum in S2 is below 100 Pa; the temperature TE 2 is 275°C-290°C; the TI 1 The time is 0.5h-2h.
[0029] Preferably, the rate of slowly heating in S3 is 2°C / min; the temperature TE 3 is 100°C-106°C; the temperature TE 4 is 170°C-176°C; the TI 2 The time is 1h-3h; the temperature TE 5 It is 290℃-296℃.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention controls the proportion of components and particle size of the composite negative ion powder so that the negative ions of the fabric can be continuously released. Introducing negative ion powder into the fabric can eliminate odor and play an antibacterial and antimicrobial role. The appropriate ratio can maximize the performance of the composite negative ion powder and release it in a long-lasting and stable manner, thereby improving the antibacterial effect. If the particle size of the composite negative ion powder is too large, the specific surface area of the composite negative ion powder in contact with the air will be reduced, which will lead to a decrease in the release efficiency of negative ions. If the particle size is too small, agglomeration will occur, affecting the final release of negative ions, thereby reducing the sustained antibacterial performance. The final negative ion release of the fabric before washing is 8000 / cm 3 After 30 washes, the negative ion release is 5500 / cm 3 .
[0032] 2. The present invention improves the antibacterial ability of fabrics by changing the dosage of composite negative ion powder and the parameter conditions of synthesizing composite antibacterial agents. A single antibacterial agent has insufficient antibacterial ability and cannot achieve a good antibacterial effect. The composite antibacterial agent prepared by reacting nano titanium dioxide, silver ions and copper nitrate in a reactor can effectively improve the antibacterial effect of the antibacterial agent; controlling the dosage of the composite antibacterial agent can effectively inhibit bacterial growth and reduce odor, while maintaining good air permeability and softness of the fabric; the composite negative ion powder and the composite antibacterial agent have a synergistic effect, and the two can jointly promote the improvement of the antibacterial performance of the fabric, so that the antibacterial effect of the fabric after washing is still very good. The bactericidal rate of the fabric before final washing against Escherichia coli is 100%, and the bactericidal rate against Staphylococcus aureus is 99.9%; the bactericidal rate of the fabric after 50 washes against Escherichia coli is 99.4%, and the bactericidal rate against Staphylococcus aureus is 95.7%.
[0033] 3. The present invention improves the bursting strength of the fabric by preparing an improved dispersant, changing the dosage of the coupling agent mixture and the ratio of the components in the coupling agent mixture. Adding glutaraldehyde to the mixture of polyvinyl alcohol fatty acid ester and polyvinyl alcohol for cross-linking reaction can effectively improve the performance of the dispersant, so that the dispersion of each component in the synthetic fiber process is more uniform and no agglomeration will occur; the coupling agent mixture can enhance the bonding force between the components and improve the physical strength of the fabric. If the dosage of the coupling agent mixture is too large, it may have an adverse effect on the structure of the fiber itself, resulting in a decrease in the strength of the fiber, and long-term use may reduce the durability of the fabric. The final bursting strength of the fabric is 366N.
[0034] 4. The present invention improves the wear resistance of the fabric by controlling the dosage of ethylene glycol and catalytic aids, as well as the temperature and time of the esterification polycondensation reaction. The parameter conditions for synthesizing ethylene terephthalate are controlled so that the material can maintain good performance; too high a temperature for esterification polycondensation may cause thermal degradation of the polymer chain, molecular chain breakage, and a decrease in the molecular weight of the final product, affecting the strength of the fabric; too low a temperature may cause the esterification reaction to proceed slowly, the polycondensation rate to decrease, and the polymerization reaction may not be fully carried out, resulting in insufficient molecular weight of the product, and poor wear resistance and durability of the fabric. The fabric was not damaged after 50 washes.
[0035] 5. The present invention improves the elongation at break of the fabric by controlling the parameter conditions in the textile process. When the temperature is too high, the molecular chain of the polymer is prone to thermal degradation, resulting in a decrease in molecular weight, which affects the mechanical properties of the fiber. High temperature will also cause certain components in the polymer to decompose and produce volatile substances. Uneven solidification may occur during the cooling process, forming surface defects. When the temperature of the melt is too low, the viscosity of the polymer increases, resulting in poor melt fluidity, making it difficult to evenly stretch into fibers, and problems such as spinneret blockage and melt fracture may occur, even leading to spinning failure. The final elongation at break of the fabric is 9.5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a graph of the elongation at break of Example 56, Examples 61-62, Examples 64-67, Examples 69-70 and Comparative Examples 8-9 of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Specific reference Figure 1 The present invention provides a negative ion antibacterial polyester fiber fabric and a preparation method thereof. The technical scheme is as follows:
[0039] Example 1
[0040] Tourmaline powder, quartz powder and carbon fiber are uniformly mixed in a weight ratio of 3:2:1 to obtain composite negative ion powder, and the particle size of the composite negative ion powder is 450 nm.
[0041] Gamma-aminopropyltriethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl)aluminate were uniformly mixed in a weight ratio of 5:3:7 to obtain a coupling agent mixture.
[0042] Preparation of composite antibacterial agent:
[0043] 6 parts of nano titanium dioxide, 1 part of silver ions and 2 parts of copper nitrate were placed in 15 parts of deionized water and stirred for 1 hour, then transferred to a reaction kettle and reacted at 175° C. for 10 hours, cooled to room temperature and centrifuged and dried to obtain the composite antibacterial agent.
[0044] Preparation of improved dispersant:
[0045] 1 part of polyvinyl alcohol fatty acid ester and 5 parts of polyvinyl alcohol are put into 10 parts of deionized water, and stirred evenly to obtain a dispersant mixture; 0.6 parts of glutaraldehyde are added to the dispersant mixture, and stirred evenly to obtain a precursor; the precursor is put into a reactor for cross-linking reaction at a temperature of 125° C. for 150 minutes, and then cooled to room temperature and centrifuged and dried to obtain the improved dispersant.
[0046] Preparation of negative ion antibacterial polyester fiber fabric:
[0047] S1: 40 parts of terephthalic acid, 14 parts of ethylene glycol and 0.08 parts of a catalyst promoter are placed in a beaker and stirred for 1 hour to obtain a mixture A; the mixture A is transferred to an esterification polycondensation reactor and reacted at 220° C. for 1.5 hours to obtain ethylene terephthalate;
[0048] S2: adding 4 parts of composite anion powder, 1.1 parts of composite antibacterial agent, 0.7 parts of improved dispersant and 1 part of coupling agent mixture to the ethylene terephthalate, stirring until uniformly mixed to obtain mixture B; transferring the mixture B to an esterification polycondensation reactor, reacting at 260° C. for 50 min, then adjusting the esterification polycondensation reactor to vacuum, heating to 275° C. for polycondensation for 0.5 h, cooling and pelletizing to obtain polyester chips;
[0049] S3: drying the polyester chips and transferring them to a vacuum drum, slowly heating them to 100°C for pre-crystallization for 100 minutes, then heating them to 170°C for 1 hour, and then putting them into a spinning machine for spinning at 290°C with a spinning speed of 3100 m / min to obtain negative ion antibacterial polyester fibers; weaving the negative ion antibacterial polyester fibers to obtain the negative ion antibacterial polyester fiber fabrics.
[0050] Embodiment 2-8
[0051] Referring to the parameter conditions of the preparation method in Example 1, the specific differences are shown in Table 1.
[0052] Comparative Example 1
[0053] The parameters and conditions of the preparation method in Example 1 are referred to, except that only tourmaline powder is added as the negative ion powder.
[0054] Example 9 Negative ion release test
[0055] The negative ion release of Examples 1-8 and Comparative Example 1 was measured according to GB / T 30128-2013 “Detection and Evaluation of Negative Ion Generation of Textiles”. The results are shown in Table 1.
[0056] Table 1 Parameter conditions and negative ion release test of Examples 1-8 and Comparative Example 1
[0057]
[0058]
[0059] As can be seen from Table 1, in Comparative Example 1, only tourmaline powder was added as negative ion powder, and the negative ion release was significantly lower than that of the fabric added with composite negative ion powder. This is because single tourmaline powder cannot provide enough negative ions, so the performance of negative ion powder is improved by mixing with quartz powder and carbon fiber and changing the ratio. In Examples 1-8, when the weight ratio of tourmaline powder, quartz powder and carbon fiber is changed and the particle size of the composite negative ion powder remains unchanged, the negative ion release of the fabric before washing first increases and then decreases, from 5400 / cm 3 Increased to 6700 pieces / cm 3 Reduced to 4400 / cm 3 When the weight ratio of tourmaline powder, quartz powder and carbon fiber is 5:2:1, the negative ion release of Example 2 reaches the highest, and the negative ion release before washing is 6700 / cm 3 After 30 washes, the negative ion release is 3300 / cm 3 This is because by mixing the three materials, the performance of releasing negative ions can be effectively improved, odor can be eliminated and antibacterial and antibacterial effects can be achieved. The appropriate ratio can maximize the performance of the composite negative ion powder and release it in a long-lasting and stable manner; when the weight ratio of tourmaline powder, quartz powder and carbon fiber is 5:2:1, and the particle size of the composite negative ion powder is changed, the negative ion release of the fabric before washing increases from 6700 / cm 3 Increased to 8000 pieces / cm 3 Reduced to 6900 / cm 3 When the particle size of the composite anion powder is 550 nm, the anion release of Example 6 reaches the highest, and the anion release before washing is 8000 / cm 3 After 30 washes, the negative ion release is 5500 / cm 3 This is because if the particle size is too large, the specific surface area of the composite negative ion powder in contact with the air will be reduced, resulting in a decrease in the release efficiency of negative ions. If the particle size is too small, agglomeration will occur, affecting the final release of negative ions, thereby reducing the sustained antibacterial performance.
[0060] Examples 10-22
[0061] Referring to the parameter conditions of the preparation method in Example 6, the difference lies in that the amount of the composite negative ion powder, the parameter conditions for synthesizing the composite antibacterial agent, and the amount of the composite antibacterial agent are changed. The specific differences are shown in Table 2.
[0062] Table 2 Parameter conditions of Example 6 and Examples 10-22
[0063]
[0064]
[0065] Comparative Example 2
[0066] Refer to the parameter conditions of the preparation method in Example 6, except that no composite negative ion powder is added.
[0067] Comparative Example 3
[0068] Refer to the parameter conditions of the preparation method in Example 6, except that only nano titanium dioxide is used as the antibacterial agent.
[0069] Example 23 Antimicrobial Ability Test
[0070] The antibacterial properties of Example 6, Examples 10-22 and Comparative Examples 2-3 were tested in accordance with GB / T 20944.3-2008 “Evaluation of Antibacterial Properties of Textiles”. The results are shown in Table 3.
[0071] Table 3 Antibacterial ability test of Example 6, Examples 10-22 and Comparative Examples 2-3
[0072]
[0073]
[0074] It can be seen from Table 3 that in Comparative Example 2, no composite negative ion powder was added, and the antibacterial performance of the fabric was very poor; in Comparative Example 3, only nano titanium dioxide was added, and it was found by comparison that the antibacterial effect was significantly inferior to that of other embodiments. The bactericidal rate of Escherichia coli before washing was 98.7%, and the bactericidal rate of Staphylococcus aureus was 97.3%. After 50 washes, the bactericidal rate of Escherichia coli was 91.2%, and the bactericidal rate of Staphylococcus aureus was 85.4%. This is because the antibacterial ability of a single antibacterial agent is insufficient and a good antibacterial effect cannot be achieved. The antibacterial performance can be improved by synthesizing a composite antibacterial agent. In Example 6 and Examples 10-22, when the amount of the composite negative ion powder, the amount of nano titanium dioxide, silver ions, and copper nitrate are changed, the reaction temperature and the amount of the composite antibacterial agent remain unchanged, the antibacterial effect of the fabric is first enhanced and then weakened. When the amount of the composite negative ion powder is 6 parts, the antibacterial effect of Example 10 is the best, the bactericidal rate of Escherichia coli before washing is 99.4%, the bactericidal rate of Staphylococcus aureus is 98.9%, the bactericidal rate of Escherichia coli after 50 washings is 98.7%, and the bactericidal rate of Staphylococcus aureus is 94.7%; when the amount of the composite negative ion powder is 6 parts, changing the nano titanium dioxide When the dosage of titanium oxide, the dosage of silver ions, copper nitrate, the reaction temperature and the dosage of the composite antibacterial agent remain unchanged, the antibacterial effect of the fabric first increases and then weakens. When the dosage of nano titanium dioxide is 8 parts, the antibacterial effect of Example 12 is the best, the bactericidal rate of Escherichia coli before washing is 99.5%, the bactericidal rate of Staphylococcus aureus is 99.1%, the bactericidal rate of Escherichia coli after 50 washes is 98.8%, and the bactericidal rate of Staphylococcus aureus is 94.8%; when the dosage of the composite negative ion powder is 6 parts and the dosage of nano titanium dioxide is 8 parts, the dosage of silver ions, the dosage of copper nitrate, the reaction temperature and When the dosage of the composite antibacterial agent remains unchanged, the antibacterial effect of the fabric is best when the dosage of silver ions is 3 parts. In Example 14, the bactericidal rate of Escherichia coli before washing is 99.6%, and the bactericidal rate of Staphylococcus aureus is 99.3%. The bactericidal rate of Escherichia coli after 50 washes is 99.0%, and the bactericidal rate of Staphylococcus aureus is 95.0%; when the dosage of the composite negative ion powder is 6 parts, the dosage of nano titanium dioxide is 8 parts, and the dosage of silver ions is 3 parts, the dosage of copper nitrate is changed, and the reaction temperature and the dosage of the composite antibacterial agent remain unchanged, the antibacterial effect of the fabric is best when the dosage of copper nitrate is 4 parts. In Example 16 The sterilization rate of Escherichia coli before washing is 99.8%, and the sterilization rate of Staphylococcus aureus is 99.5%. The sterilization rate of Escherichia coli after 50 washings is 99.1%, and the sterilization rate of Staphylococcus aureus is 95.2%. When the dosage of composite negative ion powder is 6 parts, the dosage of nano titanium dioxide is 8 parts, the dosage of silver ion is 3 parts, and the dosage of copper nitrate is 4 parts, the reaction temperature is changed, and the dosage of composite antibacterial agent remains unchanged, the antibacterial effect of the fabric is best when the reaction temperature is 180°C. The sterilization rate of Escherichia coli in Example 18 before washing is 99.9%, and the sterilization rate of Staphylococcus aureus is 99.7%, the bactericidal rate of Escherichia coli after 50 washings is 99.3%, and the bactericidal rate of Staphylococcus aureus is 95.5%; when the dosage of the composite negative ion powder is 6 parts, the dosage of nano titanium dioxide is 8 parts, the dosage of silver ions is 3 parts, the dosage of copper nitrate is 4 parts, and the reaction temperature is 180°C, when the dosage of the composite antibacterial agent is changed, the antibacterial effect of the fabric is best when the dosage of the composite antibacterial agent is 1.3 parts. The bactericidal rate of Escherichia coli in Example 21 before washing is 100%, and the bactericidal rate of Staphylococcus aureus is 99.9%. The bactericidal rate of Escherichia coli after 50 washings is 99.4%, and the bactericidal rate of Staphylococcus aureus is 95.7%. This is because too much composite negative ion powder may make the fabric harder or rougher, affecting the wearing comfort, and too little composite negative ion powder It may lead to the release effect of negative ions is not obvious, the antibacterial ability of the fabric is weak, the long-lasting antibacterial performance after washing is poor, and it is difficult to achieve the expected effect; the composite antibacterial agent prepared by reacting nano titanium dioxide, silver ions and copper nitrate in a reactor can effectively improve the antibacterial effect of the antibacterial agent, so that the fabric can still be effectively antibacterial after washing. Controlling the dosage of the composite antibacterial agent can effectively inhibit bacterial growth and reduce odor, while keeping the fabric with good air permeability and softness. Too little composite antibacterial agent cannot achieve effective antibacterial effect, and too much composite antibacterial agent may cause the fabric to harden and even irritate the skin; composite negative ion powder and composite antibacterial agent have a synergistic effect, and the two can jointly promote the improvement of the antibacterial performance of the fabric, so that the antibacterial effect of the fabric after washing is still very good. .
[0075] Embodiment 24-40
[0076] Referring to the parameter conditions of the preparation method in Example 21, the difference lies in controlling the parameter conditions for preparing the improved dispersant, changing the amount of the coupling agent mixture and the ratio of the components in the coupling agent mixture, and the specific differences are shown in Table 4.
[0077] Table 4 Parameter conditions of Example 21 and Examples 24-40
[0078]
[0079]
[0080]
[0081] Comparative Example 4
[0082] The parameters and conditions of the preparation method in Example 21 are referred to, except that no improved dispersant is added.
[0083] Comparative Example 5
[0084] The parameters and conditions of the preparation method in Example 21 are referred to, except that no coupling agent mixture is added.
[0085] Example 41 Bursting Strength Test
[0086] According to GB / T 19976-2005, the bursting strength of Example 21, Examples 24-40 and Comparative Examples 4-5 were tested. The results are shown in Table 5.
[0087] Table 5 Bursting strength test of Example 21, Examples 24-40 and Comparative Examples 4-5
[0088]
[0089] It can be found from Table 5 that in Comparative Example 4, no improved dispersant is added, and the bursting strength of the fabric is low and the mechanical properties are poor. This is because without the addition of the dispersant, the components are easily agglomerated during the synthesis process, which ultimately affects the mechanical properties of the fabric; in Comparative Example 5, no coupling agent mixture is added, and the bursting strength of the fabric is also relatively low. This is because without the addition of the coupling agent, the components are not tightly combined, which ultimately reduces the mechanical properties of the fabric. In Example 21 and Examples 24-40, when the amount of polyvinyl alcohol fatty acid ester, the amount of glutaraldehyde, the reaction temperature, the amount of improved dispersant, the weight ratio of γ-aminopropyltriethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl)aluminate and the amount of coupling agent mixture are changed, the bursting strength of the fabric first increases and then decreases, rising from 326N to 334N and then decreasing to 325N. When the amount of polyvinyl alcohol fatty acid ester is 5 parts, the bursting strength of Example 25 is the highest, with a bursting strength of 334N; when the amount of polyvinyl alcohol fatty acid ester is 5 parts, the bursting strength of Example 25 is the highest, with a bursting strength of 334N; when the amount of polyvinyl alcohol fatty acid ester is 5 parts, the bursting strength of Example 25 is the highest, with a bursting strength of 334N. When the amount of glutaraldehyde is 5 parts and the amount of glutaraldehyde is 0.8 parts, the reaction temperature, the amount of the improved dispersant, the weight ratio of γ-aminopropyl triethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl) aluminate and the amount of the coupling agent mixture remain unchanged, the bursting strength of the fabric is the highest when the amount of glutaraldehyde is 0.8 parts, and the bursting strength of Example 28 is 338N; when the amount of polyvinyl alcohol fatty acid ester is 5 parts and the amount of glutaraldehyde is 0.8 parts, the reaction temperature is changed, the amount of the improved dispersant, the weight ratio of γ-aminopropyl triethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl) aluminate and the amount of the coupling agent mixture remain unchanged When the weight ratio and the amount of the coupling agent mixture remain unchanged, the bursting strength of the fabric is the highest when the reaction temperature is 130°C, and the bursting strength of Example 30 is 344N; when the amount of polyvinyl alcohol fatty acid ester is 5 parts, the amount of glutaraldehyde is 0.8 parts, the reaction temperature is 130°C, the amount of the improved dispersant is changed, the weight ratio of γ-aminopropyltriethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl)aluminate and the amount of the coupling agent mixture remain unchanged, the bursting strength of the fabric is the highest when the amount of the improved dispersant is 1.1 parts, and the bursting strength of Example 34 is 355N; When the amount of polyvinyl alcohol fatty acid ester is 5 parts, the amount of glutaraldehyde is 0.8 parts, the reaction temperature is 130°C, the amount of improved dispersant is 1.1 parts, the weight ratio of γ-aminopropyl triethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl)aluminate is changed, and the amount of coupling agent mixture remains unchanged, the bursting strength of the fabric is the highest when the weight ratio is 6:3:6, and the bursting strength of Example 37 is 360N; when the amount of polyvinyl alcohol fatty acid ester is 5 parts, the amount of glutaraldehyde is 0.8 parts, the reaction temperature is 130°C, the amount of improved dispersant is 1.1 part, the weight ratio of γ-aminopropyl triethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl)aluminate is 6:3:6. When the amount of the coupling agent mixture is changed, the bursting strength of the fabric increases first and then decreases. It is the highest when the amount of the coupling agent mixture is 3 parts. The bursting strength of Example 39 is 366N. This is because the addition of glutaraldehyde to the mixture of polyvinyl alcohol fatty acid ester and polyvinyl alcohol for cross-linking reaction can effectively improve the performance of the dispersant, so that the dispersion of each component in the synthetic fiber process is more uniform, and there will be no agglomeration phenomenon, thereby improving the mechanical properties of the fabric; the coupling agent mixture can enhance the bonding force between the components and improve the physical strength of the fabric. If the amount of the coupling agent mixture is too large, it may have an adverse effect on the structure of the fiber itself, resulting in a decrease in the strength of the fiber, and long-term use may reduce the durability of the fabric. .
[0090] Examples 42-58
[0091] Referring to the parameter conditions of the preparation method in Example 39, the difference lies in that the amount and type of ethylene glycol and catalyst aid, as well as the temperature and time of the esterification polycondensation reaction are changed. The specific differences are shown in Table 6.
[0092] Table 6 Parameters and conditions of Example 39 and Examples 42-58
[0093]
[0094]
[0095] Comparative Example 6
[0096] The parameters of the preparation method in Example 39 are as follows, except that the temperature TE 1 is 300℃, temperature TE 2 At 350°C, TI 1 The duration is 4 hours.
[0097] Comparative Example 7
[0098] The parameters of the preparation method in Example 39 are as follows, except that the temperature TE 1 is 150℃, temperature TE 2 At 200°C, TI 1 The time is 0.1h.
[0099] Example 59 Wear resistance test
[0100] Example 39, Examples 42-58 and Comparative Examples 6-7 were washed according to the standard of GBPT 8629-2001, and the wear degree of the fabrics after washing 50 times was tested. The results are shown in Table 7.
[0101] Table 7 Wear resistance test of Example 39, Examples 42-58 and Comparative Examples 6-7
[0102]
[0103]
[0104] It can be found from Table 7 that the excessively high esterification polycondensation temperature and the excessively long time in Comparative Example 6 lead to a decrease in the wear resistance of the fabric after washing 50 times. This is because the excessively high esterification polycondensation temperature may cause thermal degradation of the polymer chain and molecular chain breakage, resulting in a decrease in the molecular weight of the final product, affecting the strength of the fabric; the excessively low esterification polycondensation temperature and the excessively short time in Comparative Example 7 will also affect the wear resistance of the fabric. This is because too low a temperature will cause the esterification reaction to proceed slowly, the polycondensation rate to decrease, and the polymerization reaction may not be fully carried out, resulting in insufficient molecular weight of the product, and poor wear resistance and durability of the fabric. In Examples 39 and 42-58, when the amount of ethylene glycol, the type of catalyst, the amount of catalyst, the temperature TE 1 , Temperature TE 2 and TI 1 When the time is constant, the wear resistance of the fabric is the strongest when the amount of ethylene glycol is 18 parts; when the amount of ethylene glycol is 8 parts, changing the type of catalyst, the amount of catalyst, and the temperature TE 1 , Temperature TE 2 and TI 1 When the time is constant and the catalyst is titanium tetrachloride, the wear resistance of Example 46 is the highest. This is because the appropriate catalyst can promote the esterification reaction and ultimately improve the strength of the fiber fabric. When the amount of ethylene glycol is 8 parts and the catalyst is titanium tetrachloride, the amount of the catalyst is changed and the temperature TE 1 , Temperature TE 2 and TI 1 When the time is constant, the wear resistance of the fabric reaches the highest when the catalyst dosage is 0.1 parts. This is because the appropriate amount of catalyst can ensure the full esterification reaction, so that the performance of ethylene terephthalate reaches the highest; when the amount of ethylene glycol is 8 parts, the catalyst is titanium tetrachloride, and the amount of catalyst is 0.1 parts, the temperature TE is changed. 1 , temperature TE 2 and TI 1 When the time is constant, the wear resistance of Example 50 is the highest, the fabric has less broken yarn and fewer holes; when the amount of ethylene glycol is 8 parts, the catalyst is titanium tetrachloride, the amount of the catalyst is 0.1 parts, the temperature TE 1 To 224℃, change the temperature TE 2 , T.I. 1When the time is constant, the wear resistance of Example 54 is the highest, the fabric has less broken yarns and no holes; when the amount of ethylene glycol is 8 parts, the catalyst is titanium tetrachloride, the amount of the catalyst is 0.1 parts, and the temperature TE 1 The temperature TE is 224℃. 2 At 285°C, change TI 1 Time, Example 56 has the highest wear resistance, and the fabric is not damaged after 50 washes. This is because the parameter conditions for synthesizing ethylene terephthalate are controlled so that the material can maintain good performance, and the appropriate reaction temperature and time are conducive to the smooth progress of the reaction, which can not only avoid the problem of molecular weight reduction caused by too high or too low temperature, but also ensure that the reaction is fully carried out to obtain a high molecular weight polymer, ultimately improving the wear resistance of the fabric and enhancing the mechanical properties.
[0105] Examples 60-70
[0106] Referring to the parameter conditions of the preparation method in Example 56, the difference is that the parameter conditions in the textile process are changed. The specific differences are shown in Table 8.
[0107] Table 8 Parameters and conditions of Example 56 and Examples 60-70
[0108] Example <![CDATA[Temperature TE 3 / ℃]]> <![CDATA[Temperature TE 4 / ℃]]> <![CDATA[TI 2 Time / h]]> <![CDATA[Temperature TE 5 / ℃]]> Embodiment 56 100 170 1 290 Embodiment 60 102 170 1 290 Embodiment 61 104 170 1 290 Embodiment 62 106 170 1 290 Embodiment 63 104 172 1 290 Embodiment 64 104 174 1 290 Embodiment 65 104 176 1 290 Embodiment 66 104 174 2 290 Embodiment 67 104 174 3 290 Embodiment 68 104 174 2 292 Embodiment 69 104 174 2 294 Embodiment 70 104 174 2 296
[0109] Comparative Example 8
[0110] The parameters of the preparation method in Example 56 are as follows, except that the temperature TE 3 is 150℃, temperature TE 4 At 250°C, TI 2 Time is 5h, temperature TE 5 is 400℃.
[0111] Comparative Example 9
[0112] The parameters of the preparation method in Example 56 are as follows, except that the temperature TE 3 is 50℃, temperature TE 4 At 100°C, TI 2 Time is 0.5h, temperature TE 5 is 200℃.
[0113] Example 71 Elongation at break test
[0114] According to GB / T 3916-1997 "Test method for breaking strength and elongation of single yarn", the breaking elongation of Example 56, Examples 60-70 and Comparative Examples 8-9 were tested. The results are shown in Table 9 and Figure 1 shown.
[0115] Table 9 Elongation at break test of Example 56, Examples 60-70 and Comparative Examples 8-9
[0116] Example Elongation at break / % Embodiment 56 7.9 Embodiment 60 8.2 Embodiment 61 8.4 Embodiment 62 8.1 Embodiment 63 8.6 Embodiment 64 8.7 Embodiment 65 8.5 Embodiment 66 9.0 Embodiment 67 8.9 Embodiment 68 9.2 Embodiment 69 9.5 Embodiment 70 9.3 Comparative Example 8 6.8 Comparative Example 9 7.3
[0117] From Table 9 and Figure 1 It can be found that the high temperature and long spinning time in Comparative Example 8 will seriously affect the strength of the fabric, and the elongation at break is only 6.8%. This is because when the temperature is too high, the molecular chain of the polymer is prone to thermal degradation, resulting in a decrease in molecular weight, which affects the mechanical properties of the fiber. High temperature will also cause certain components in the polymer to decompose and produce volatile substances, which may cause uneven solidification during the cooling process and form surface defects; in Comparative Example 9, the low temperature and short time will also affect the elongation at break of the fabric. This is because when the temperature of the melt is too low, the viscosity of the polymer increases, which will lead to poor melt fluidity and difficulty in uniformly stretching into fibers. Problems such as spinneret blockage and melt fracture may occur, and even lead to spinning failure. From Table 9 and Figure 1 It was found that in Example 56 and Examples 60-70, when the temperature TE was changed 3 , temperature TE 4 ,TI 2 Time and temperature TE 5 When the temperature TE is constant, the elongation at break of the fabric increases first and then decreases, rising from 7.9% to 8.4% and then falling to 8.1%. 3 When the temperature is 104°C, the elongation at break of Example 61 is the highest, which is 8.4%. 3 To 104℃, change the temperature TE 4 , T.I. 2 Time and temperature TE 5 When the temperature TE 4 When the temperature is 174°C, the elongation at break of Example 64 is the highest, which is 8.7%. 3 is 104°C, temperature TE 4 to 174°C, changing TI 2 Time, temperature TE 5 When the elongation at break of the fabric is constant, the elongation at break of the fabric is 2 The highest elongation at break was 9.0% when the time was 2h. 3 is 104°C, temperature TE 4 174℃, TI 2 Time is 2h, change temperature TE 5 When the elongation at break of the fabric is 5The highest temperature is 294°C. The elongation at break of Example 69 is 9.5%. This is because too high or too low temperature may lead to a decrease in fiber quality. The appropriate temperature and time ensure good melt fluidity and uniform fiber, resulting in a high elongation at break, improved mechanical properties, and avoided melt degradation or equipment damage.
[0118] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A negative ion antibacterial polyester fiber fabric, characterized in that: The negative ion antibacterial polyester fiber fabric comprises the following raw materials by weight: Composite negative ion powder: 4-8 parts; Composite antibacterial agent: 1.1-1.5 parts; Improved dispersant: 0.7-1.5 parts; Coupling agent mixture: 1-5 parts; Terephthalic acid: 40 parts; Ethylene glycol: 14-22 parts; Catalyst aid: 0.08-0.12 parts.
2. The negative ion antibacterial polyester fiber fabric according to claim 1, characterized in that: The composite negative ion powder is a mixture of tourmaline powder, quartz powder and carbon fiber; the weight ratio of the tourmaline powder, the quartz powder and the carbon fiber is 3-9:2:1; and the particle size of the composite negative ion powder is 450nm-650nm.
3. The negative ion antibacterial polyester fiber fabric according to claim 1, characterized in that: The coupling agent mixture is a mixture of γ-aminopropyltriethoxysilane, tetrabutyl titanate and tri(2-vinylphenyl)aluminate; the weight ratio of the γ-aminopropyltriethoxysilane, the tetrabutyl titanate and the tri(2-vinylphenyl)aluminate is 5-7:3:7-5.
4. The negative ion antibacterial polyester fiber fabric according to claim 1, characterized in that: The catalyst promoter is one of antimony trioxide, titanium tetrachloride and zinc chloride.
5. A method for preparing a negative ion antibacterial polyester fiber fabric, characterized in that: The negative ion antibacterial polyester fiber fabric according to claim 1 is prepared by a preparation method comprising the following steps: S1: 40 parts of terephthalic acid, 14-22 parts of ethylene glycol and 0.08-0.12 parts of a catalyst promoter are placed in a beaker and stirred for 1 hour to obtain a mixture A; the mixture A is transferred to an esterification polycondensation reactor and reacted at a temperature of TE1 for 1.5 hours to obtain ethylene terephthalate; S2: adding 4-8 parts of composite anion powder, 1.1-1.5 parts of composite antibacterial agent, 0.7-1.5 parts of improved dispersant and 1-5 parts of coupling agent mixture to the ethylene terephthalate, stirring until uniformly mixed to obtain mixture B; transferring the mixture B to an esterification polycondensation reactor, reacting at 260° C. for 50 min, then adjusting the esterification polycondensation reactor to vacuum, heating to temperature TE2, polycondensing for TI1 time, cooling and pelletizing to obtain polyester chips; S3: drying the polyester chips and transferring them to a vacuum drum, slowly heating them to a temperature TE3 for pre-crystallization for 100 minutes, then heating them to a temperature TE4 and maintaining them for a time of TI2, and then putting them into a spinning machine for spinning at a temperature TE5 with a spinning speed of 3100 m / min to obtain negative ion antibacterial polyester fibers; weaving the negative ion antibacterial polyester fibers to obtain the negative ion antibacterial polyester fiber fabrics.
6. The method for preparing a negative ion antibacterial polyester fiber fabric according to claim 5, characterized in that: The temperature TE1 in S1 is 220°C-232°C.
7. The method for preparing a negative ion antibacterial polyester fiber fabric according to claim 5, characterized in that: The preparation method of the composite antibacterial agent in S2 is as follows: 6-10 parts of nano titanium dioxide, 1-5 parts of silver ions and 2-6 parts of copper nitrate are placed in 15 parts of deionized water and stirred for 1 hour, then transferred to a reactor and reacted at 175°C-190°C for 10 hours, cooled to room temperature and centrifuged to obtain the composite antibacterial agent.
8. The method for preparing a negative ion antibacterial polyester fiber fabric according to claim 5, characterized in that: The preparation method of the improved dispersant described in S2 is: put 1-9 parts of polyvinyl alcohol fatty acid ester and 5 parts of polyvinyl alcohol into 10 parts of deionized water, stir evenly to obtain a dispersant mixture; add 0.6-1 part of glutaraldehyde to the dispersant mixture, stir evenly to obtain a precursor; put the precursor into a reactor for cross-linking reaction at a temperature of 125°C-140°C for 150 minutes, cool to room temperature and centrifuge to obtain the improved dispersant.
9. The method for preparing a negative ion antibacterial polyester fiber fabric according to claim 5, characterized in that: The vacuum in S2 is below 100 Pa; the temperature TE2 is 275° C.-290° C.; and the TI1 time is 0.5 h-2 h.
10. The method for preparing a negative ion antibacterial polyester fiber fabric according to claim 5, characterized in that: The slow heating rate in S3 is 2°C / min; the temperature TE3 is 100°C-106°C; the temperature TE4 is 170°C-176°C; the TI2 time is 1h-3h; and the temperature TE5 is 290°C-296°C.
Citation Information
Patent Citations
Anion, antimicrobial and anti-mite compound polyester functional fiber and manufacturing method thereof
CN107217325A
Lavender flavor type sleeping-aiding negative ion melt-blown non-woven fabric wall paper base paper and manufacturing method thereof
CN105821583A
Preparation method of fabric with functions of releasing negative ions, killing bacteria, removing stink and repelling mosquitoes
CN109706540A
Waterproof coating material for garden road and construction method thereof
CN109762428A
Powder containing carbon nanotubes for electrodes, electrode mixture paste, electrode for electricity storage device, and electricity storage device
CN118830106A
Cited By
Manufacturing method of high-fluffiness special-shaped hollow fiber
CN120700607A